Valorization of hazardous leather shaving dust for the fabrication of electrospun collagen/PVA/chitosan nanomats in wound care - Fatema Tujjohra; Md. Mazharul Islam; Taslim Ur Rashid; Mohammed Mizanur Rahman (Carbohydrate Polymer Technologies and Applications)
This study presents a novel strategy for utilizing chrome-tanned leather shaving dust (CSD), a hazardous industrial byproduct, by converting it into electrospun nanofibrous mats for wound healing applications. Collagen, extracted from CSD through protease-assisted enzymatic hydrolysis with a 99.98 % dechroming efficiency (reducing chromium from 7700 ppm to 4.71 ppm) and a 31 % yield, was combined with poly(vinyl alcohol) (PVA) and chitosan. Nanomats were fabricated by electrospinning and characterized using FT-IR, XRD, DSC, TGA, and SEM. The S-3 formulation (collagen/PVA ratio of 1:3 with 20 % chitosan) demonstrated optimal properties, including a nanofiber diameter of 277 nm, tensile strength of 3.7 MPa, and 90 % elongation at break, indicating suitability for skin tissue engineering. Thermal analysis revealed enhanced thermal stability, and swelling studies revealed controlled water uptake (150 % in water, 118 % in PBS). S-3 exhibited controlled biodegradation, with 57 % weight loss over three weeks in simulated body fluid. Comparative properties and wound healing performance analysis showed superior antibacterial activity against Bacillus subtilis (30 mm inhibition zone) and Escherichia coli (23 mm inhibition zone), exceeding that of existing collagen-based nanomats and commercial scaffolds. In vivo studies confirmed accelerated wound closure (12 days) compared to other collagen-based nanomats and commercial dressings (16-21 days), along with enhanced collagen deposition, and fibroblast proliferation. These findings demonstrate that CSD-derived collagen/PVA/chitosan nanomats offer a sustainable and high-performance alternative to existing wound dressings.